Molecular Docking Studies of Phytoconstituents Identified in Traditional Siddha Polyherbal Formulations Against Possible Targets of SARS-CoV-2 - Logesh Kumar Selvaraj; Geethanjali Thayumanavan; Srikanth Jeyabalan; Sugin Lal Jabaris (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2021)
The Indian Traditional Medicines System has long used Siddha polyherbal formulations for different viral diseases. The ingredients of these formulas have been proven to be antiviral. The study focuses on in silico computational evaluation of phytoconstituents of the official Siddha formulation Kabasura, Thonthasura, and Vishasura Kudineer, which were widely used in treating viral fever and respiratory infections and may influence the current SARS-CoV-2 coronary virus pandemic. Maestro interface (Schrödinger Suite, LLC, NY) was used for molecular docking studies against MPro (PDB ID 5R82, 6Y2F, and 6LU7), Nsp15 endoribonuclease (6W01), RNA-dependent RNA polymerase (6M71), and spike protein (6VW1) of SARS-CoV-2. In addition, pharmacokinetics (ADME) and safety profile prediction studies were performed to identify the best drug candidates using Qikpro and Toxicity Estimation Software Tool (T.E.S.T). A total of 36 compounds were screened, of which nine displayed strong binding affinity and drug-likeness. Luteolin and chrysoeriol produced stronger results. These nine compounds were free of oral toxicity as evaluated by the Toxicity estimation software. Based on further in vitro, in vivo, and clinical effectiveness trials, these compounds may be used for the prevention or treatment as per the Indian system of traditional medicines.